2022
DOI: 10.25259/sni_662_2022
|View full text |Cite
|
Sign up to set email alerts
|

“The most inspiring and mind-blowing meetings ever:” Highlights of the 15th SNI Baghdad Neurosurgery Online Meeting, from Participants’ Perspectives

Abstract: Background: Education by lectures has been standard for 100 years or more. Given the 21st century technology, people can connect with others around the world instantly, electronically. With the pandemic, teaching changed to one-way information transfer with the loss of interpersonal learning experience. SNI® and now SNI Digital™ have been experimenting with different forms of communication to transfer information. Methods: Using an interactive education model, a meeting for neurosurgeons in Baghdad was hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…[ 8 , 10 ] There is about one neurosurgeon for each 200,000 population, and unfortunately, some have left the country for safety. [ 4 ] This brain drain must be stopped nationally. History has shown that it is impossible for any civilization to survive with the loss of its best people.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 8 , 10 ] There is about one neurosurgeon for each 200,000 population, and unfortunately, some have left the country for safety. [ 4 ] This brain drain must be stopped nationally. History has shown that it is impossible for any civilization to survive with the loss of its best people.…”
Section: Discussionmentioning
confidence: 99%
“…They want hope for the future, the opportunity to dream for a better world, inspiration, and outstanding mentors. [ 4 ] Read the results of the recent 15 th SNI-B national meeting for more insight into the solution to the educational challenge for the developing countries. [ 4 ] The youth is the future of every country and in medicine and neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations